Endoscopic stenting for esophageal anastomoses leakage (review of literature) - A. I. Ivanov; V. A. Popov; M. V. Burmistrov (Вестник хирургии имени И.И. Грекова)
Esophageal anastomoses leakage is a serious and urgent problem of surgical complications with high mortality rates. With the development of endoscopic technologies, minimally invasive methods of treatment are widely introduced into clinical practice with the development of endoscopic technologies in various non-standard situations, including esophageal anastomoses leakage. Stenting is one of the methods of choice in this case. However, the indicators of their effectiveness differ significantly across studies. A retrospective analysis of the stenting results in this severe complication demonstrates many factors influencing the success of esophageal stent implantation. Stents are often selected without due regard to their characteristics, which may affect the results of implantation. One of the most frequent and unfavorable outcomes of stenting is stent migration, which significantly affects the prognosis of the treatment. In this regard, in Russian practice, stenting, as a method of treating for esophageal anastomoses leakage, is introduced only in some institutions. However, many complications can be avoided at present due to the development in endoscopy and the constant improvement of stent designs. The objective of this review was to highlight the main advantages and problemsof stenting in esophageal anastomoses leakage today.